Electrocatalytic Determination of Sulfite using 1-[4-(Ferrocenylethynyl)phenyl]-1-ethanone Modified Carbon Paste Electrode - BAKHSH RAOOF, JAHAN; OJANI, REZA; KARIMI-MALEH, HASAN (Asian Journal of Chemistry, 2010)
The electrochemical behaviour of sulfite studied at the surface of 1-[4-(ferrocenylethynyl)phenyl]-1-ethanone modified carbon paste electrode (4-FEPEMCPE) in aqueous media using cyclic voltammetry and double step potential chronoamperometry. It has been found that under optimum condition (pH 8) in cyclic voltammetry, the oxidation of sulfite occurred at a potential about 280 mV less positive than that unmodified carbon paste electrode. The kinetic parameters such as electron transfer coefficient, α and catalytic reaction rate constant, K´h were also determined using electrochemical approaches. The electrocatalytic oxidation peak current of sulfite shows a linear calibration curve were obtained in the range 3.0 × 10-4 M–1.2 × 10-2 M and 4.0 × 10-6 M–1.0 × 10-4 M of sulfite concentration with cyclic voltammetry (CV) and differential pulse voltammetry (DPV) methods, respectively. The detection limit (2δ) was determined as 1.4 × 10-5 M and 1.8 × 10-7 M by CV and DPV methods.